La distinzione sessuale nel magistero post-conciliare: dall'irrilevanza alla necessità ontologica - Biscardi, Angelo (Rassegna di teologia, 2017)
Sexual distinction is an anthropological issue that has had an important evolution in theology of the twentieth century. From irrelevant object it has in fact become a keystone in recovering the dignity of the body, up to become an ontological pillar of reflection on sexuality and gender issues. This contribution is intended to value the opportunities of this situation but also some problem.